Analysis of the Six Eras of the Creation of the Universe in the Holy Qur'an and the Bible: Semiotic Studies Alfred Jules Ayer - Zainul Ashri (Spiritus: Religious Studies and Education Journal, 2023)
All religions have an explanation about nature creating with their version. Talking about these kinds, this paper was not present to be correct who is true or who is false, but a process of nature creating needed to be explained with science so that it can be accepted by mind and conviction. That can be known by becoming deep through making use of logical positivism semiotics analysis by Alfred Jules Ayer. With the use of library research, comparative study, and semiotics analysis by Alfred J. Ayer, this paper has some findings, namely: comparative about nature created from Al-Qur'an and Bible, just not a doctrine of religion. But, as a result of logical positivism analysis, Alfred J. Ayer explains that nature was created during six periods (time) in Islam, and Christianity, in theology, believed that it was a creation of God. Then, the process of nature's creation during six periods (time) is very long; the truth can be verified by the findings of scientists, namely a genesis of nature created by the Big Bang incident, and then because that is dissociated between earth and sky and engender earth and interplanetary rotation in their pivot after that earth experience evolution and all of the process is ended with creating of mountains, plants, humans, and others.